Orientasi Budaya Manusia Toraja dalam Puama Suatu Tinjauan Hermeneutika Perspektif Hans-Georg Gadamer - Berthin Simega (Balai Bahasa Provinsi Bali, 2024)
This study is reviewed under hermeneutics to identify the cultural orientation of Torajan people in Puama a Hermeneutics Review of Hans-Georg Gadamer's Perspective. The information is presented orally by the storyteller, who narrates the characters' behaviors and events in puama while expressing thoughts that are pertinent to the study subject. Research data was collected through several techniques: (1) recording, (2) observation, and (3) in-depth interview. The data analysis technique used in this study is cyclical pattern technique. The results of this study show that the Torajan people have spiritual, traditional, and mythical cultural orientations. Spiritual cultural orientation in puama or Toraja folklore was found in their obedience to aluk (faith), ada’na pemali (AAP or laws of taboos). The Torajan people's submission to agreements reached through ma'kombongan (deliberation) activities can be used to identify their traditional cultural orientation. Torajan mythical cultural orientation in Toraja folklore was found in their belief in pemali (taboos/prohibitions). Puama was used to determine the Torajan cultural orientations, it is therefore imperative to be preserved as one source of Torajan knowledge and local wisdom (indigenous or local knowledge) which in turn beneficial for any stakeholders. AbstrakPenelitian ini bertujuan untuk mengungkapkan informasi tentang orientasi budaya manusia Toraja melalui pendekatan hermeneutika perspektif Hans-Georg Gadamer. Data berupa tuturan lisan dari juru cerita yang menggambarkan peristiwa dan tindakan para tokoh dalam puama yang mengandung pemikiran-pemikiran yang terarah pada fokus masalah penelitian. Data penelitian dikumpulkan melalui teknik (1) rekam, (2) observasi, dan (3) wawancara mendalam. Teknik analisis data yang digunakan dalam penelitian ini adalah teknik cyclical pattern. Temuan penelitian ini, yaitu orientasi budaya manusia Toraja adalah orientasi budaya spiritual, orientasi budaya tradisional, dan orientasi budaya mitis. Orientasi budaya spiritual manusia Toraja dalam puama atau Cerita Rakyat Toraja (CRT) ditemukan pada ketaatannya terhadap aluk, ada’ na pemali (AAP). Orientasi budaya tradisional ditemukan melalui sikap tunduk manusia Toraja pada kesepakatan melalui kegiatan ma’kombongan (musyawarah). Orientasi budaya mitis manusia Toraja dalam CRT ditemukan melalui kepercayaannya pada pemali (pantangan/larangan). Dengan teridentifikasinya orientasi budaya manusia Toraja melalui puama tersebut, puama perlu dilestarikan sebagai salah satu satu sumber pengetahuan dan kecerdasan lokal (indigenous or local knowledge) masyarakat Toraja yang dapat bermanfaat bagi pemangku kepentingan.